Pharmacophore mapping: Prediction of BCR-ABL kinase inhibitory activity of α-benzylthio chalcones - Richa Bajaj; Vikas Sharma; Vipin Kumar (Faculty of Pharmacy, Cairo University, 2014)
In this investigation, 3D pharmacophore modeling studies were performed on a diverse set of 33 α-benzylthio chalcone derivatives that demonstrate anticancer activity by blocking BCR-ABL phosphorylation in leukemic cells. Pharmacophore modeling is based on the principle of the alignment of pharmacophoric features which has been carried out on the same set of molecules. Five point pharmacophores with one negative ionizable group, one hydrophobic group and three aromatic rings as pharmacophoric features were developed. Pharmacophore hypothesis HNRRR 1501 yielded a statistically significant 3D-QSAR model with R2 value 0.9103 and was considered to be the best pharmacophore hypothesis. The selected pharmacophore model HNRRR 1501 was externally validated by predicting the activity of test set. The correlation coefficient of 0.8856 was observed between experimental and predicted activities of test set. The features of pharmacophore were expected to be useful for the design of selective BCR-ABL tyrosine kinase inhibitors.